Waterbird diversity and its influencing factors in various types of coastal wetlands in the Bohai Rim region - Mengdi FU; Jun WANG; Chunfei HOU; Junsheng LI; Jiade BAI; Yuanyuan ZHANG (Global Ecology and Conservation)
The coastal wetlands of the Bohai Rim region in China serve as critical habitats for breeding, migratory stopovers, and wintering birds along the East Asian-Australasian Flyway. This study surveyed waterbird diversity across 17 coastal wetlands in the Bohai Rim region from 2018 to 2023 to identify community composition, analyze spatial and temporal patterns, and examine the key factors influencing waterbird diversity across various wetland types. A total of 133 species belonging to 18 families and 8 orders were recorded, with migratory species comprising 85.71 % of the total. Scolopacidae, Charadriidae, and Laridae exhibited the highest species richness and abundance, respectively. The number of waterbirds and diversity indices displayed a fluctuating but overall upward trend during the study period. Estuarine wetlands had the highest waterbird diversity, tidal wetlands exhibited the greatest bird density, whereas shallow sea and island wetlands showed comparatively lower diversity and evenness. The primary factors influencing waterbird diversity, ranked by significance, were PM2.5 concentration, vegetation coverage, macrobenthic biodiversity, regional population density, and temperature. High PM2.5 concentrations were significantly associated with reduced waterbird diversity, whereas higher vegetation coverage promoted diversity by improving habitat complexity. Macrobenthic biodiversity influenced food web dynamics via predation and competition, leading to a marginally negative impact on waterbird diversity. Regional population density significantly impacted waterbird diversity in island and tidal wetlands, highlighting the necessity of establishing and managing protected areas to sustain waterbird diversity. Additionally, increased precipitation caused by climate change alters wetland water levels, indirectly impacting habitat conditions for waterbirds. Improved wetland management and pollution control are essential for preserving waterbird diversity. This study provides important insights into how air pollution, water pollution, and climate change affect waterbird diversity, emphasizing the importance of integrated management strategies for maintaining coastal wetland ecosystem stability and the health of waterbird communities.